PENGARUH PEMBERIAN AQUASYM GRADES A, B, C DAN D DAN INTERVAL PENYIRAMAN TERHADAP PERTUMBUHAN TANAMAN TEMBAKAU DELI (Nicotiana tabacum L) - Risnawati , (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This study was to determine the effect of Aquasym Grades A, B, C and D and Interval watering deli on the growth of tobacco plants (Nicotiana tabacum L). The design used was a randomized block design (RBD) with a pseudo factorial treatment are: A0 = Without Aquasym (Control), A1 = giving aquasym grade A = 5 g / polybag, gift aquasym grade A2 = B = 5 g / polybag, A3 = granting aquasym grade C = 5 g / polybag and A4 = giving aquasym grade D = 5 g / polybag, B0 = Without watering, watering every day B1 = B2 = 3 days watering, watering B3 = 5 days, B4 = watering 7 days of treatment with a combination of B0 A0, A1 B1, A1 B2 A1 B3, B4 A1, A2 B1, A2 B2, A2 B3, B4 A2, A3 B1, B2 A3, A3 B3, B4 A3, A4, B1, B2 A4 , A4 B3, B4 A4. Parameters observed that plant height (cm), stem diameter (mm), leaf length (cm), leaf width (cm), leaf thickness (mm), number of leaves (strands), wet weight (g). The results showed that the administration of treatment and interaction aquasym both treatments showed no real effect on all parameters were observed.  Keywords: Aquasym Grades A, B, C and D, interval watering, Tobacco Deli